Dinamika Peran Perempuan dalam Pendidikan Tinggi Menurut Perspektif Islam : Studi Kasus Analisis Pandangan Masyarakat Dukuh Binangun - Aeni, Delliana Fitri (IAINU Kebumen, 2025)
The existence of local culture and society's mindset towards women in higher education is the main point. Some parents prioritize boys' education and ignore girls' education, so it is not surprising that a girl's identity development is retarded. As according to Islam stated in Q.S. al-Mujadilah: 11 which means: